2007
DOI: 10.1152/ajpregu.00203.2007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of calcium balance in the sturgeonAcipenser naccarii: a role for PTHrP

Abstract: Calcium regulation in sturgeon is of special interest because they are a representative of the ancient fishes possessing mainly cartilaginous skeletons and a supposedly low calcium demand. The present study aimed to characterize the effect of a chronic absence of dietary calcium and the effect of parathyroid hormone-related protein (PTHrPA) (1-34) (7) on calcium balance in juvenile sturgeon (Acipenser naccarii). At rest, sturgeon juveniles are in net positive calcium balance, since whole body calcium uptake is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…5). The results obtained are in agreement with previous in vivo (2,10,11,19) and in vitro (9) results and indicate a mechanism consistent with hypercalcemic actions of PTHrP in fish.…”
Section: Fig 5 Calcium Uptake (J Insupporting
confidence: 91%
“…5). The results obtained are in agreement with previous in vivo (2,10,11,19) and in vitro (9) results and indicate a mechanism consistent with hypercalcemic actions of PTHrP in fish.…”
Section: Fig 5 Calcium Uptake (J Insupporting
confidence: 91%
“…This relationship has also been found in the developing stages of other fishes (Chou et al, 2002;Flik et al, 1986;Flik et al, 1985;Fuentes et al, 2007). Thus, lake sturgeon seem very capable of handling low calcium environments, at least at the concentrations tested, although there may be a lower limit of tolerable Ca 2+ concentrations.…”
Section: Influence Of Environmental Calcium On Whole-body Ca 2+ Fluxsupporting
confidence: 64%
“…In this study, lake sturgeon responded to low environmental calcium concentrations by increasing Ca 2+ uptake and decreasing efflux, whereas in high environmental calcium concentrations the opposite was true. Ca 2+ influx rates in lake sturgeon were lower than those reported in freshwater-acclimated larval tilapia [200-250nmolg -1 h -1 (Chou et al, 2002;Hwang et al, 1996)], comparable to those reported in juvenile tilapia [~110nmol h -1 g -1 ; Flik et al (Flik et al, 1986);Flik et al (Flik et al, 1985)], and higher than those reported from juvenile rainbow trout [30-60nmolh -1 g -1 (Hogstrand et al, 1994;Niyogi and Wood, 2006) (Flik et al, 1986;Flik et al, 1985)], and higher than those in Adriatic sturgeon [~1nmolh -1 g -1 (Fuentes et al, 2007)]. In this study, it is likely that acclimation time also influenced the magnitude of Ca 2+ -influx, as influx rates in rainbow trout (Oncorhynchus mykiss) subjected to low calcium environments have been demonstrated to be initially high, and to gradually decrease with the duration of acclimation (Perry and Wood, 1985).…”
Section: Influence Of Environmental Calcium On Whole-body Ca 2+ Fluxmentioning
confidence: 61%
“…PTH administration induced hypercalcemia in fugu ( Tetraodon nigrividans ) by inducing both osteoblast and osteoclast function and by decreasing scale calcium content [94]. Genes homologous to the mammalian PTH-related peptides (PTHrP) were found in teleosts, they are more widely expressed [95], they increase calcium uptake in sturgeon ( Acipenser nacarii ) [96]and were shown to play different roles in craniofacial development in zebrafish [97]. Blocking PTH signaling through the use of a PTH/PTHrP antagonist resulted in a decreased hypercalcemic response to estradiol in sea bream ( Sparus aurata ) [98].…”
Section: Discussionmentioning
confidence: 99%